Impaired Expression of the Inducible cAMP Early Repressor Accounts for Sustained Adipose CREB Activity in Obesity - Favre, Dimitri; Le Gouill, Eric; Fahmi, Denis; Verdumo, Chantal; Chinetti-Gbaguidi, Giulia; Staels, Bart; Caiazzo, Robert; Pattou, François; Lê, Kim-Anne; Tappy, Luc; Regazzi, Romano; Giusti, Vittorio; et al. (Diabetes (New York, N.Y.), 2011)
Increase in adipose cAMP-responsive element binding protein (CREB) activity promotes adipocyte dysfunction and systemic insulin resistance in obese mice. This is achieved by increasing the expression of activating transcription factor 3 (ATF3). In this study, we investigated whether impaired expression of the inducible cAMP early repressor (ICER), a transcriptional antagonist of CREB, is responsible for the increased CREB activity in adipocytes of obese mice and humans. Total RNA and nuclear proteins were prepared from visceral adipose tissue (VAT) of human nonobese or obese subjects and white adipose tissue (WAT) of C57Bl6-Rj mice that were fed with normal or high-fat diet for 16 weeks. The expression of genes was monitored by real-time PCR, Western blotting, and electromobility shift assays. RNA interference was used to silence the expression of Icer. The expression of Icer/ICER was reduced in VAT and WAT of obese humans and mice, respectively. Diminution of Icer/ICER was restricted to adipocytes and was accompanied by a rise of Atf3/ATF3 and diminution of Adipoq/ADIPOQ and Glut4/GLUT4. Silencing the expression of Icer in 3T3-L1 adipocytes mimicked the results observed in human and mice cells and hampered glucose uptake, thus confirming the requirement of Icer for appropriate adipocyte function. Impaired expression of ICER contributes to elevation in CREB target genes and, therefore, to the development of insulin resistance in obesity.